Retreatability of Bioceramic Endodontic Sealers: a Review - Kostadin I. Zhekov; Vessela P. Stefanova (Folia Medica, 2020)
In 2009 a new type of endodontic sealers was introduced to the market. The so called “bioceramic” sealers are a promising alternative to the present golden standard of root canal fillings. Now a decade later, still very little is known about the ability to remove these sealers in cases of non-surgical endodontic retreatment (NSER). There are only a limited number of articles that provide such information. The commonly used hand files are not efficient in removing thoroughly the sealer from the main canal walls. Machine driven files are much easier and faster alternative to the hand ones, but are still not able to ensure complete removal. Although ultrasonics can be applied only in the straight portion of the main canal, they raise the efficacy of sealer removal. Photon-initiated photoacoustic streaming (PIPS) is another way to enhance the removal of bioceramics. Solvents like chloroform and orange oil are effective in softening gutta-percha, but not the bioceramics. This article reviews the available scientific data concerning removal of bioceramic materials in the context of a NSER.